Rain-rate estimation in the presence of hail using S-band specific differential phase and other radar parameters - Bringi, V. N., author; Aydin, K., author; Liu, L., author; American Meteorological Society, publisher (Colorado State University. Libraries, 1995)
Multiparameter radar measurements were made during a heavy rainfall event accompanied by hail in Colorado. Rainfall rates Rand accumulation Σ for this event were estimated using S-band specific differential phase KDP, reflectivity factor Zh, and X-band specific attenuation AH3. These estimates were compared with measurements from a ground-based rain gauge. Both R-KDP and R-AH3 relations were in good agreement with the rain gauge data, that is, less than 10% difference in the rainfall accumulations. The R-Z relation produced similar results only when ZH was truncated at 55 dBZ. This study demonstrates the potential of KDP for estimating rainfall rates in severe storms that may have rain-hail mixtures.